Characteristics of local guinea fowl (Numida meleagris) production and breeding systems in northern Côte d’Ivoire’s Poro region (International Journal of Scientific Research and Management (IJSRM), 2021)
Local guinea fowl are the second most abundant poultry resource in the area, behind local chickens, and they are exploited in an uncontrolled system that affects production. Rural poultry farmers in 12 villages in the departments of Korhogo and Sinématiali participated in a descriptive study on their agricultural system. 35 local guinea fowl owners were asked to complete a semi-structured questionnaire. The findings show that in the Poro region, local méléagriculture is practiced solely in a large-scale system. This practice is restricted for men (94 %), supported by family members (68.60 %), and seen as secondary by the respondents (68.57 %). Farmers, planters, and retailers make up most of them (85.71 %). The original breeding nucleus was made up of eggs (80%) and female guinea fowl (14.28 %). Guinea fowls lay the first eggs at an average age of 7 months (54.28 percent), with the early ones around 6 months (20 %). The flocks are tiny (average of 25 guinea fowl) and are made up of mature (55.69%), young (23.11%), and early (11.40%) guinea fowl. All these guinea fowl have pearled feathers and are primarily grey (71.43 %). They live in rudimentary shelters and forage for food on the streets. The main causes of guinea fowl mortality (68.59 %) were rain and humidity, which had an impact on productivity. This region had the highest percentage of livestock items for sale (62.84%). The socio-economic position of the farmer, the farming method, and the utilization of chicken products were used to identify three agricultural sub-systems.